Unveiling anaerobic soccer training: comparing its effects with small-sided games on youth performance enhancement - Trio Hisbi Muttahid Ahmad; I Dewa Made Aryananda Wijaya Kusuma; Bayu Agung Pramono; Mochammad Ilham Ramadhani; Waristra Tyo Nirwansyah (Pedagogy of Physical Culture and Sports, 2025)
Background and Study Aim. Soccer is a high-intensity sport that requires players to maintain optimal physical performance over an extended period. This has led to the development of various training methods to enhance both aerobic and anaerobic energy systems. Small-Sided Games (SSG) is a popular training method in soccer, as it improves both technical skills and fitness. However, its effectiveness in developing anaerobic capacity still requires further investigation. Therefore, this study aims to compare the effects of Anaerobic Soccer Training (AnST) and SSG on aerobic and anaerobic performance in young soccer players.